Numerical modelling of a geosynthetic reinforced steep slope subjected to seismic loading - Castorina Silva Vieira (2011)
In recent earthquakes the performance of reinforced soil retaining walls was diverse. The Hyogoken-Nambu (Kobe) Earthquake caused serious damage to conventional masonry retaining walls, unreinforced concrete gravity-type retaining walls and cantilever-type steel-reinforced concrete retaining walls, while geogrid-reinforced soil retaining walls, having a full-height concrete facing, performed very well during the earthquake [1]. On the other hand, the Chi-Chi earthquake, in Taiwan, caused serious damage to reinforced-soil retaining walls using keystones as facing [2]. In this work the two-dimensional finite difference program Fast Lagrangian Analysis of Continua FLAC [3] was used to model the seismic response of a geogrid reinforced steep slope constructed in the North of Portugal. This structure was built in the Portuguese main itinerary, IP3, and is part of a reestablishment. The reinforced slope has an extension of about 206.2 m and the reinforced soil area reaches a maximum height of about 19.6 m. The slope behaviour was observed during 13 months, which includes three months of construction period. The analysis of monitoring information of this geogrid reinforced steep slope and the numerical simulation of its construction are briefly presented. The seismic behaviour of this structure is analysed using FLAC program. Earthquake ground motions artificially generated with the program SIMQKE [4] were considered as seismic loading. The permanent displacements and reinforcement tensile forces are analysed and compared. The numerical simulation of seismic loading showed a good performance of the reinforced steep slope. Since the structure is an overpass embankment, permanent vertical settlements can be the most disquieting factor. The residual reinforcement tensile forces remain smaller than the long term design strength of the geogrids.